Percursos da cidade em João Antônio - Júlio Cezar Bastoni da Silva (Estudos de Literatura Brasileira Contemporânea, 2013)
This article proposes an analysis of the representation of the city in João Antônio’s literature, having as main reference the book Ô, Copacabana!, published in 1978. The city in João Antônio’s writings seems to be composed by the particular language and focus of the narrator, who wants himself identified to the lower classes, emulating the talk of the excluded people by a linguistic treatment, with its syntactic, rhythmic and vocabulary implications, building a point of view apart from the representations of the upper classes. Thus, João Antônio tries to represent the city through the focus of those social classes, which results in the preference for unknown places, marginal from official images.